The development strategy of durian fruit-based ecotourism: A case study of Rancamaya Village in Bogor, Indonesia - Liza Indina; Sodikin; Lina Warlina (Indonesian Journal of Applied Environmental Studies, 2025)
Legok Petir place in Rancamaya Village, South Bogor District, has a strategic role in efforts to improve the surrounding community's welfare sustainably. With a long history of durian fruit, Rancamaya has the nickname of "Rancamaya Durian Village". The purpose of this study is to evaluate the feasibility of ecotourism development and find strategies that can be carried out related to how to develop it. The analysis method used the guidelines of the Operation Area Object and​​ Object of Natural Tourism Attractions (Analisis Daerah Operasi Objek dan Daya Tarik Wisata Alam / ADO-ODTWA) of the Director General of Forest Protection and Nature Conservation-2003, Community-Based Ecotourism Enterprise (CBEE) to produce aspects that have a high feasibility category, as well as SWOT analysis to determine the effective strategy to maximize the existing potential and prepare to face challenges. The aspects analyzed are 1) tourist attractions, 2) conditions around the area, 2) management and services, 4) accessibility, and 5) facilities and infrastructure. The results of the study show that the Rancamaya area has feasibility as a tourist area of Durian Village with a tourist attraction scoring of 81.0%, the condition around the area of 66.7%, management and service of 65.5%, accessibility of 90 % and facilities and infrastructure of 61.1%. Meanwhile, the development strategy of the Rancamaya tourist area is influenced by policies, institutions, coaching, and socialization.